Genetic Control of Facultative Parthenocarpy in Nicotiana tabacum L. (19th April 2019) - Dexter-Boone, Abigail; Humphry, Matt; Shi, Rui; Lewis, Ramsey S
Abstract: Investigation of parthenocarpy, the production of fruit without fertilization, in multiple plant species could result in development of technologies for conferring seedless fruits and increased stability of fruit formation in economically important plants. We studied parthenocarpy in the model species Nicotiana tabacum L., and observed variability for expression of the trait among diverse genetic materials. Parthenocarpy was found to be partially dominant, and a single major quantitative trait locus on linkage group 22 was found to control the trait in a doubled haploid mapping population derived from a cross between parthenocarpic cigar tobacco cultivar "Beinhart 1000" and nonparthenocarpic flue-cured tobacco cultivar, "Hicks." The same genomic region was found to be involved with control of the trait in the important flue-cured tobacco cultivar, "K326." We also investigated the potential for the production of maternal haploids due to parthenogenesis in parthenocarpic tobacco seed capsules. Maternal haploids were not observed in parthenocarpic capsules, suggesting a requirement of fertilization for maternal haploid production due to parthenogenesis in N. tabacum .